2007
DOI: 10.1038/sj.icb.7100117
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis secretory proteins CFP‐10, ESAT‐6 and the CFP10:ESAT6 complex inhibit lipopolysaccharide‐induced NF‐κB transactivation by downregulation of reactive oxidative species (ROS) production

Abstract: Mycobacterium tuberculosis (Mtb) causes death of 2-3 million people annually and is considered one of the most successful intracellular pathogens to persist inside the host macrophage. Recent studies have implicated the role of RD-1 region of Mtb genome in the mycobacterial pathogenesis. The role of RD-1-encoded secretory proteins of Mtb in modulation of macrophage function has not been investigated in detail. Here we show that RD-1 encoded two major secretory proteins, namely, culture filtrate protein-10 kDa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 71 publications
2
61
0
5
Order By: Relevance
“…ESAT6-CFP10 manufacturing was overseen by regulators. The expression and purification of the recombinant protein were conducted by standard protocols (12,13). The purity of this recombinant fusion protein was analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and high-performance liquid chromatography (HPLC) and was Ն95% purity in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ESAT6-CFP10 manufacturing was overseen by regulators. The expression and purification of the recombinant protein were conducted by standard protocols (12,13). The purity of this recombinant fusion protein was analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and high-performance liquid chromatography (HPLC) and was Ն95% purity in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol was reviewed, approved, and registered at ClinicalTrials.gov under registration no. NCT01999231 (12).…”
Section: Methodsmentioning
confidence: 99%
“…Studies from our lab have shown that CFP-10 and ESAT-6 downregulates the production of reactive oxygen species (ROS) inside the macrophages; which in turn dampens the NF-ĸB transactivation property (Ganguly et al, 2008a, Ganguly et al, 2008b. The inhibition of ROS production was greater with the CFP10:ESAT6 complex compared to the individual proteins.…”
Section: Macrophage Subversion By Cfp10 and Esat6mentioning
confidence: 83%
“…Los bacilos tuberculosos responden a situaciones de estrés por agotamiento de nutrientes, pH ácido, especies reactivas de oxígeno y nitrógeno causado por su crecimiento en los macrófagos (7,8,14) . Para responder a estos estímulos, las micobacterias secretan enzimas como ESAT-6 y CFP-10 (2,15) , que en las células del hospedero, actúan en los procesos de necrosis, tales como la lisis del epitelio alveolar y membranas de los macrófagos, induce la fragmentación del ADN y la permeabilidad de la membrana de las mitocondrias (15) .…”
unclassified
“…The bacilli respond to stress conditions due to nutrient depletion, acid pH, and reactive oxygen and nitrogen species, caused by their growth in macrophages (7,8,14) . In order to respond to these stimuli, mycobacteria secrete enzymes, such as ESAT-6 and CFP-10 (2,15) , which in the cells of the host, act in necrosis processes, such as lysis of alveolar epithelium and membranes of macrophages, induction of DNA fragmentation and permeability of mitochondrial membranes (15) .…”
mentioning
confidence: 99%